The Effectivity of Supplementation Artemisia vulgaris for Adenocarcinoma Mammae Chemotherapy to Reduce CD 34 and Tumor Massa Diameter (Study in C3H Mice Given Adriamycin - Cyclophosphamide Chemotherapy) - Bayu Teguh Saputro; Selamat Budijitno (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Introduction: Breast cancer is still a major health problem in the world. In the case of breast cancer, surgery is the main treatment option besides chemotherapy, radiation, and immunotherapy such as Artemisia vulgaris (AV). AV is cytotoxic selectively acts as a supplement to breast adenocarcinoma chemotherapy given the Adriamycin-Cyclophosphamide regimen, to improve chemotherapy response.The study was aimed to proving AV extract enhances the chemotherapy response in C3H mice with adenocarcinoma mammae given Adriamycin-Cyclophosphamide Chemotherapy. Method: This study used Post test only control group design on 24 females C3H mice that were randomly selected and divided into four groups: group K (control), P1 (chemotherapy), P2 (extract), and P3 (combination). Adenocarcinoma mammae comes from the inoculation of donor mice. Chemotherapy of Adriamycin 60 mg / m 2 and Cyclophosphamide 600 mg / m 2 were given in two cycles. AV 13 mg (0.2 ml) was given once daily orally. CD34 were evaluated by imunohistochemical staining and tumor mass diameter were counted by calipers. Result: The microvascular density CD34 and tumor mass diameter were obtained in groups of K, P1, P2, P3 respectively 60.76 ± 1.5; 39.70 ± 2.00; 57.10 ± 1.29; 35.26 ± 2.06 and 12.52 ± 1.49; 6.20 + 1.04; 9,94 + 1.21; 3.94 + 0.76. Statistical analysis showed significant differences in CD34 between groups K vs P1, P2, P3 (p = 0.001, p = 0.014, p = 0.001), P1 vs P2 and P3 (p = 0.001, p = 0.033) and P2 (P = 0.001). Tumor mass diameter between groups K vs P1, P2, P3 (p=0.001; p=0.014; p=0,001), P1 with P2 (p= 0.001) P1 with P3 (p = 0.033) and P2 with P3 (p = 0.001). Correlation analysis between CD34 with tumor mass diameter was found to have significant correlation (p = 0.001 and r = 0.932). Conclusion: Artemisia vulgaris is a potential to reduce angiogenesis in terms of decreasing the microvascular density CD34 and tumor mass diameter of adenocarcinoma mammae of C3H mice treated with Adriamycin-Cyclophosphamide chemotherapy and can improve the effectivity.